2020
DOI: 10.2807/1560-7917.es.2020.25.50.2001884
|View full text |Cite
|
Sign up to set email alerts
|

Occupation- and age-associated risk of SARS-CoV-2 test positivity, the Netherlands, June to October 2020

Abstract: High coronavirus incidence has prompted the Netherlands to implement a second lockdown. To elucidate the epidemic’s development preceding this second wave, we analysed weekly test positivity in public test locations by population subgroup between 1 June and 17 October 2020. Hospitality and public transport workers, driving instructors, hairdressers and aestheticians had higher test positivity compared with a reference group of individuals without a close-contact occupation. Workers in childcare, education and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 4 publications
7
39
1
Order By: Relevance
“…In accordance with the present results, the food production/processing sector has been identified by European Centre for Disease Prevention and Control (ECDC) as a potential hotspot for COVID-19 clusters or outbreaks [10]. Several distinct job characteristics could expose individuals to a high risk of contracting COVID-19, such as exposure to the virus due to the proximity to others, face-to-face discussions, and interactions with external customers or the public [11][12][13][14]. While there are certainly employers in the food/catering industry who provide high-quality jobs, by and large, the sector consists of very low-wage jobs with few benefits, and many restaurant workers live in poverty or near-poverty [15][16][17].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In accordance with the present results, the food production/processing sector has been identified by European Centre for Disease Prevention and Control (ECDC) as a potential hotspot for COVID-19 clusters or outbreaks [10]. Several distinct job characteristics could expose individuals to a high risk of contracting COVID-19, such as exposure to the virus due to the proximity to others, face-to-face discussions, and interactions with external customers or the public [11][12][13][14]. While there are certainly employers in the food/catering industry who provide high-quality jobs, by and large, the sector consists of very low-wage jobs with few benefits, and many restaurant workers live in poverty or near-poverty [15][16][17].…”
Section: Discussionsupporting
confidence: 82%
“…In that context, apart from the food production/processing sector, the education, childcare sectors, sales, and retail sectors, bus/coach/taxi drivers and construction workers have also been proposed as occupations with a high potential for exposure and outbreaks. Another study, performed from June to October 2020 in the Netherlands, found that hospitality and public transport workers, driving instructors, hairdressers, and aestheticians had higher test positivity compared with a reference group of individuals without a close-contact occupation [11]. However, in this study, certain occupations with high SARS-CoV-2 infection risk, such as food processing, were not identified, given the limited number of occupational categories in the questionnaire [11].…”
Section: Discussioncontrasting
confidence: 55%
“…At least two recent studies did not find associations between race and mortality outcomes among those able to access hospital care [100,101], contrary to findings of most other research, including this review. More recent studies have also examined a wider range of sociodemographic factors in relation to COVID-19 infection such as primary spoken language [96], and additional studies have examined those factors less often assessed in early reports, such as educational attainment [90,93,97], occupation [97,102,103], and marital status [93]. Contrasting the early findings from one study included in our analysis, at least two studies indicate that cohabitation and larger households are associated with COVID-19 infection and mortality [103,104].…”
Section: Plos Onementioning
confidence: 75%
“…Evidence coming from retrospective and cross-sectional studies early in the pandemic [28][29] and from larger surveillance studies relating to the second peak of the pandemic, strongly supports minimal transmission rates in European day-care centres and primary schools, both for pupils and educational staff [30][31][32][42][43][44]. Significantly, this finding remains consistent also in areas of high COVID-19 background incidence and after systematic contact testing of each paediatric index case.…”
Section: Introductionmentioning
confidence: 75%